The Role of Management Information Systems in Organizational Fund Management: Study on the Student Executive Board of the Faculty of Economics and Business, Tadulako University - Rudy Usman; Andi Indriani Ibrahim; Misbahul Aulia; Yuly Azahra; Dian Safita; Nini Andriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research discusses the role of Management Information Systems (SIM) in managing student organization funds, with a research focus on the Student Executive Board of the Faculty of Economics and Business (BEM FEB), Tadulako University (UNTAD). The main problem raised is the suboptimal financial system of student organizations that are still managed manually, as well as the lack of transparency and accountability in fund management. The purpose of this research is to explore how SIM is used in practice, to deal with the challenges faced, and its contribution to the efficiency and transparency of the organization's financial governance. This research used a qualitative approach with a case study method, and data collection techniques of semi-structured interviews and documentation. The results show that although the use of SIM is still limited to simple applications such as Excel and Google Drive, the system has helped the management in recording finances, preparing reports, and monitoring expenses. SIM also encourages a more accountable and collaborative organizational culture. However, limited human resources, infrastructure, and digital literacy are significant challenges in optimizing the system. This research contributes to understanding the role of information technology implementation at the student organization level and recommends the need for institutional support and continuous training to strengthen digital-based managerial capacity in the campus environment.